Integrating Multicultural Education in Islamic Primary Boarding Schools: Roles and Educational Implications - Jumadia Jumadia; Harli Harli; Julhadi Julhadi (Ahlussunnah: Journal of Islamic Education, 2026)
This study examines the role of Islamic primary educational institutions, particularly madrasah and boarding-based schools, in promoting multicultural education. It focuses on both academic and non-academic strategies in fostering inclusive, tolerant, and diversity-aware student character. The study aims to explore how multicultural values are integrated through curriculum design, extracurricular activities, and social interactions within the school environment. This research employs a qualitative approach using content analysis. Data were collected from relevant books, journal articles, and academic documents related to multicultural education and Islamic schooling. The data were systematically analyzed through coding, categorization, and interpretation to identify key themes, institutional roles, and educational practices. The findings reveal that these institutions play a significant role in developing multicultural education. Academically, inclusive teaching approaches are implemented to respect cultural and religious diversity. Non-academically, activities such as arts, sports, social projects, and intercultural dialogue contribute to strengthening students’ tolerance, empathy, and collaborative skills. This study highlights the importance of curriculum reinforcement, teacher capacity building, and community engagement in enhancing the effectiveness of multicultural education. The findings contribute to strengthening the discourse on Islamic education and its role in fostering social cohesion in diverse societies.